Mária Kovács - The History of the CEU
Interview with Prof. Mária Kovács about the history of the CEU. Questions are asked by Béla Nové. She teaches at the Department of History and Nationalism Studies Program since 1996. Prof. Kovács talks in this interview about the departments, the programs and the courses CEU offers. She describes the specificity of and the challenges provided by the Nationalism Studies Program as well as its early history as a program at CEU. She also talks about the composition of the body of students in the program and the ever increasing diversity and promotion of tolerance within the department. The heavy emphasis on the study of Roma issues within the wider framework of minority studies within the program is also explained in this interview.